Cosmids from the Vollmer-Yanofsky library identified with a chromosome VII probe. - P. Ballario; G. Morelli; E. Sporeno; G. Macino (Fungal Genetics Reports, 1989)
In microorganisms, genes can often be cloned directly by complementation of mutants with a genomic library.